Integrative proteomics and metabolomics reveal the stress response of semicarbazide in the sea cucumber Apostichopus japonicus - Lu, Lixin; Ren, Lihua; Jiang, Lisheng; Xu, Xiaohui; Wang, Weijun; Feng, Yanwei; Li, Zan; Yang, Jianmin; Sun, Guohua (Frontiers in Marine Science, 2022)
Semicarbazide (SMC), also known as carbamoyl hydrazide, is a key intermediate for the organic synthesis of drugs, pesticides, and a panoply of other applications. It is also regarded as a landmark metabolite of nitrofurazone, a banned veterinary drug. SMC produced in different ways will eventually enter the ocean and become an emerging marine pollutant, affecting the physiological metabolism, behavioral activities, and even survival of aquatic organisms. Sea cucumbers are sediment-feeding organisms, and their risk of exposure to pollutants has attracted increasing attention. In this study, an integrated proteomic and metabolomic approach was used to investigate the responses of Apostichopus japonicus treated with SMC (3.72 g/L) for 72 h. After SMC treatment, the proteins and metabolites of A. japonicus intestine changed significantly. The results showed that 342 differentially expressed proteins were identified, of which 174 were upregulated, 168 were downregulated, and 74 differentially expressed metabolites, of which 62 were upregulated and 12 were downregulated. These differential proteins and metabolites were primarily involved in energy metabolism, lipid metabolism, signal transduction, immune regulation, autophagy, and apoptosis. On the basis of a combination of proteomic and metabolomic data, a hypothetical network of proteins, metabolites, and pathways in sea cucumbers was also described; the resulting network indicated several significant biological activities in response to SMC. This work offers a thorough analysis of the intricate mechanisms by which sea cucumbers respond to SMC stress and indicates numerous possible indicators for further research on creatures exposed to SMC. Further, our results provide scientific guidance for pollution control of Apostichopus japonicus culture to ensure healthy breeding.